PENINGKATAN HASIL BELAJAR MERODA MELALUI MODEL PEMBELAJARAN LANGSUNG - DWIYANTARI, ONENG (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract   For most students this phenomenon is only used as objects and not subjects. As a result, the material presented is not completely absorbed in the absence of feedback between the material provided by the teacher and received by the students, so the impact on learning outcomes of students who are not optimal. It is seen from the assessment that has been done, there are 19 students or 44.19% gain criterion of "less" and 24 students received a score above 70 or 55.81% have criteria of "being" and "good". That means still less than the Minimum Graduation Criteria (KKM) ≥ 70 which is desired. So this study using direct learning model for learning is the learning model that is specifically designed to develop students' learning of procedural knowledge and declarative knowledge can be taught step by step. The purpose of this study was to determine the increase in psychomotor skills of students in the cart wheel  motion using direct learning model. Research conducted by researchers is the experimental study using action research approach within the scope of the class of the class action research (PTK). In this study the use of sampling techniques designation (cluster random sampling). The subject of this study were students of class VC Kedurus V the state of elementary school  Surabaya. This is because all the problems that have emerged this class. The total number of students are 43 people with the characteristics of sex, men are as many as 20 people, while the women as many as 23 people. The results are as follows: In cycle 1, KKM surpassed by 27 students or 64.28% said the application of learning methods not yet complete. In the second cycle, KKM surpassed by 30 students or 70.09%. Because a greater percentage of 70%, then this can be said to complete. To roll back an increase in the initial study results of 39.73% and the final study results are at 81.70%. So learn to Cart Wheel the test results of students before and after receiving a direct method that is equal to 41.97%. Keywords: Learning Outcomes, Cart Wheel, method.